Evidences Suggestive of Reincarnation based on Indian Beliefs - Kumaar, Sidhharrth S. (European Journal of Applied Sciences, 2023)
Ancient scriptures in Indian culture strongly support the concept of reincarnation. Researchers have travelled from place to place to study cases and concluded that over 92% of them were true. This article discusses the various pieces of evidence that strongly suggest the existence of rebirth, describes the characteristics specific to reincarnated individuals, and also methods adapted to prove the existence of reincarnation. The article, however, does not claim that reincarnation exists, for it is still debatable.